Atividade, saberes e valores: análise discursivo-ergológica do processo de gestão de uma cooperativa autogestionária do MST - Alencastro, Lucia Helena (2019)
The present work was developed in the Terra Livre cooperative, located in the Settlement of Contestado, in the town of Lapa, state of Paraná. It is based on the hypothesis that the formative context consolidated in the activity of struggle, resistance and conquest of the means to carry out the work in the settlements of the Movement of Landless Rural Workers (MST) (Brazilian acronym for Movimento dos Trabalhadores Rurais Sem Terra) articulates specific knowledge and values that contribute to the development of self-management in its cooperatives. It follows from this hypothesis, as a general objective, to address the discourse about the work activity developed by the managers of the Terra Livre cooperative in order to understand the different types of knowledge and values circulating in the organization's management space. From the theoretical-methodological point of view, the assumptions of Discourse Analysis were articulated to the foundations of Ergology. The constitution of the corpus brought together normative documents of the self-managed cooperativism and texts extracted from the interviews with the cooperative managers. For the purpose of corpus selection, the notions of instituted knowledge and invested knowledges proposed by Schwartz, as well as the notions of discourse and interdiscursivity, discursive formation and discursive community, formulated by Maingueneau, were initially considered. Afterwards, the research objectives and the resulting questions were resumed. From these definitions, work management was delimited as the field of research and, within this field, a discursive space was outlined by two different discursive formations: self-management and heteromanagement. The corpus analysis allowed us to understand the importance of the knowledge derived from the MST for the development of the management activity of the cooperative through the self-management bias, with the identification of a support network of these values beyond the economic development. It was also identified the predominance of the knowledge invested in the management activity in the sense of learn-by-doing, as well as the low investments in internal normative prescription. Although these aspects produce some difficulties for daily work, at the same time, they contribute to the production of knowledge in a very broad way, which encourages the organizational management to be thought under a pedagogical point of view